2019
DOI: 10.1017/inp.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Russian-olive (Elaeagnus angustifolia) genetic diversity in the western United States and implications for biological control

Abstract: Invasions can be genetically diverse, and that diversity may have implications for invasion management in terms of resistance or tolerance to control methods. We analyzed the population genetics of Russian-olive (Elaeagnus angustifoliaL.), an ecologically important and common invasive tree found in many western U.S. riparian areas. We found three cpDNA haplotypes and, using 11 microsatellite loci, identified three genetic clusters in the 460 plants from 46 populations in the western United States. We found hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The total genomic DNA was extracted from silica gel dried leaves collected according to the protocol described by Doyle and Doyle (1990) or the cetrimonium bromide (CTAB) based method reported by Doyle and Doyle (1990). Out of the 11 pairs of SSR primers of Elaeagnus designed and tested by Gaskin et al (2019), nine pairs of primers suitable for this study were selected, named Ro887, Ro218, Ro236, Ro20, Ro721, Ro325, Ro749, Ro851 and Ro833. The SSR markers showing high efficiency in closely related species were chosen to explore the genetic diversity our two study species.…”
Section: Dna Extraction and Polymerase Chain Reaction (Pcr) Amplifica...mentioning
confidence: 99%
See 1 more Smart Citation
“…The total genomic DNA was extracted from silica gel dried leaves collected according to the protocol described by Doyle and Doyle (1990) or the cetrimonium bromide (CTAB) based method reported by Doyle and Doyle (1990). Out of the 11 pairs of SSR primers of Elaeagnus designed and tested by Gaskin et al (2019), nine pairs of primers suitable for this study were selected, named Ro887, Ro218, Ro236, Ro20, Ro721, Ro325, Ro749, Ro851 and Ro833. The SSR markers showing high efficiency in closely related species were chosen to explore the genetic diversity our two study species.…”
Section: Dna Extraction and Polymerase Chain Reaction (Pcr) Amplifica...mentioning
confidence: 99%
“…Simple‐sequence repeat (SSR) markers have the advantage of accurate and rapid detection even with the existence of co‐dominance, multiple alleles, high polymorphism and variability and hence, can be used for species identification, establishment of well‐known germplasm resources, and determination of differences between varieties (Ahmad et al 2018, Patzak et al 2019, Prysiazhniuk et al 2019). SSR markers (nine pairs) have been designed to compare the genetic diversity of E. angustifolia in Asia, Europe and North America, and to prevent its biological invasion in the North America as reported by Gaskin et al (2019). In this study, we used these nine SSR markers reported to evaluate the relationship between E. moorcroftii and E. angustifolia .…”
Section: Introductionmentioning
confidence: 99%
“…Many successful invasive species also have traits such as a fast reproductive cycle or rapid maturity, that promote or enhance the opportunities for adaptation ( Baker, 1974 ; Sakai et al, 2001 ). Comparing genetic variation of the plant between populations in the native and introduced ranges and identifying genetic lineages can assist with the selection of better adapted candidate biocontrol agents that are more likely to be effective ( Moody et al, 2016 ; Kwong et al, 2017 ; Gaskin et al, 2019 ; Morin, 2020 ). Understanding the spatial distribution of distinct genetic entities can also inform management design for improved control, such as where buffer zones are positioned to avoid different variants moving to new areas ( Moore et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Russian olive used as control plants originated from several locations in Wyoming, Idaho and Montana. The plants correspond to two different genotypes that are present in North America: H1 and H4 (recently identified by Gaskin et al, 2019). The quarantine testing was done from mid-June to July of each year.…”
mentioning
confidence: 99%
“…The only plant species that supported a population of the mite, A. angustifoliae was Russian olive, with no apparent preference for population used in the tests. Since the separation of the genotypes is recent (Gaskin et al, 2019), it was unknown during the earlier testing to which genotype each individual tree belonged and thus all control plant data were lumped together. Two live individuals of A. angustifoliae were recorded in the same year (2014) on 2/67 sampled shoots of Elaeagnus commutata (Table 1).…”
mentioning
confidence: 99%